Cultural Guidelines for Commercial Production of Interiorscape Syngonium - Jianjun Chen; Dennis B. McConnell; Kelly C. Everitt (EDIS)
This article is intended to describe common cultivars in the foliage plant industry, provide guidelines for their culture and interior use, and list physiological problems that may be encountered during production and interiorscape use. This document is ENH 993, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date April 2005.